Gut-Liver Immune Traffic: Deciphering Immune-Pathogenesis to Underpin Translational Therapy - Bozward, Amber G.; Ronca, Vincenzo; Osei-Bordom, Daniel; Oo, Ye Htun (Frontiers in Immunology, 2021)
The tight relationship between the gut and liver on embryological, anatomical and physiological levels inspired the concept of a gut-liver axis as a central element in the pathogenesis of gut-liver axis diseases. This axis refers to the reciprocal regulation between these two organs causing an integrated system of immune homeostasis or tolerance breakdown guided by the microbiota, the diet, genetic background, and environmental factors. Continuous exposure of gut microbiome, various hormones, drugs and toxins, or metabolites from the diet through the portal vein adapt the liver to maintain its tolerogenic state. This is orchestrated by the combined effort of immune cells network: behaving as a sinusoidal and biliary firewall, along with a regulatory network of immune cells including, regulatory T cells and tolerogenic dendritic cells (DC). In addition, downregulation of costimulatory molecules on hepatic sinusoids, hepatocytes and biliary epithelial cells as well as regulating the bile acids chain also play a part in hepatic immune homeostasis. Recent evidence also demonstrated the link between changes in the gut microbiome and liver resident immune cells in the progression of cirrhosis and the tight correlation among primary sclerosing cholangitis (PSC) and also checkpoint induced liver and gut injury. In this review, we will summarize the most recent evidence of the bidirectional relationship among the gut and the liver and how it contributes to liver disease, focusing mainly on PSC and checkpoint induced hepatitis and colitis. We will also focus on completed therapeutic options and on potential targets for future treatment linking with immunology and describe the future direction of this research, taking advantage of modern technologies.